2020
DOI: 10.1038/s41598-020-65374-6
|View full text |Cite
|
Sign up to set email alerts
|

Of Mice and Monkeys: Neuroprotective Efficacy of the p38 Inhibitor BIRB 796 Depends on Model Duration in Experimental Glaucoma

Abstract: Glaucoma is a group of optic neuropathies associated with aging and sensitivity to intraocular pressure (IOP). Early progression involves retinal ganglion cell (RGC) axon dysfunction that precedes frank degeneration. Previously we demonstrated that p38 MAPK inhibition abates axonal dysfunction and slows degeneration in the inducible microbead occlusion model of glaucoma in rat. Here, we assessed the neuroprotective effect of topical eye delivery of the p38 MAPK inhibitor BIRB 796 in three models of glaucoma (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…We showed that intraocular delivery of CMP during a period of elevated IOP ameliorated deficits in the retinotopic representation of active transport in the superior colliculus ( Figures 5 , 6 ), the primary target for RGC axons in rodents. Elevated IOP is an important risk factor for RGC degeneration and vision loss in glaucoma ( Susanna et al, 2015 ), and slowing or stopping transport deficits in experimental models of glaucoma slows subsequent degenerative stages that occur in longer periods of microbead glaucoma, including axon degeneration followed by RGC body elimination ( Lambert et al, 2011 , 2017 , 2020 ; Dapper et al, 2013 ). Interestingly, this same CMP (CMP 03A) promoted repair of the corneal epithelial layer following acute injury ( Baratta RO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that intraocular delivery of CMP during a period of elevated IOP ameliorated deficits in the retinotopic representation of active transport in the superior colliculus ( Figures 5 , 6 ), the primary target for RGC axons in rodents. Elevated IOP is an important risk factor for RGC degeneration and vision loss in glaucoma ( Susanna et al, 2015 ), and slowing or stopping transport deficits in experimental models of glaucoma slows subsequent degenerative stages that occur in longer periods of microbead glaucoma, including axon degeneration followed by RGC body elimination ( Lambert et al, 2011 , 2017 , 2020 ; Dapper et al, 2013 ). Interestingly, this same CMP (CMP 03A) promoted repair of the corneal epithelial layer following acute injury ( Baratta RO.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important observation since the colliculus represents the primary target for RGCs in the rodent visual system. Furthermore, experimental interventions that slow or abate transport degradation also prevent subsequent stages of degeneration (Lambert et al, 2011(Lambert et al, , 2017(Lambert et al, , 2020Dapper et al, 2013;Bernardo-Colón et al, 2018). With this in mind, we measured whether treatment with CMP could reduce the progression of anterograde transport degradation with IOP elevation.…”
Section: Calkinsmentioning
confidence: 99%
“…This is so as well in experimental models of glaucoma, which generally rely upon inducible or transgenic-related elevations in IOP [13,14]. In rodents, experimental interventions that slow or prevent loss of anterograde transport to RGC projection sites in the brain also impede axon degeneration in the optic nerve and cell body loss in the retina [5,[15][16][17]. Without intact transport, axons undergo Wallerian or Wallerian-like degeneration [1].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated IOP induces deficits in axon transport along the optic nerve ( Lambert et al, 2017 , 2020 ) and reduction in NaV1.2 protein levels in RGCs ( Risner et al, 2020 ) after 4 weeks of ocular hypertension. In contrast, changes in RGC electrical signaling occur earlier after eIOP.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IOP induces deficits in axon transport along the optic nerve (Lambert et al, 2017(Lambert et al, , 2020 (Risner et al, 2018). In both the brain and the retina, dendritic pruning is linked to the production of C1q and the subsequent initiation of the classical complement cascade by CD11b + cells (Stevens et al, 2007).…”
Section: Cell Reportsmentioning
confidence: 99%